A Method for Isolating and Culturing Skin Cells: Application to Endothelial Cells, Fibroblasts, Keratinocytes, and Melanocytes From Punch Biopsies in Systemic Sclerosis Skin - Henrot, Pauline; Laurent, Paôline; Levionnois, Emeline; Leleu, Damien; Pain, Catherine; Truchetet, Marie-Elise; Cario, Muriel (Frontiers in Immunology, 2020)
Systemic Sclerosis (SSc) is a complex auto-immune connective tissue disease combining inflammatory, vasculopathic and fibrotic manifestations. Skin effectively recapitulates the main pathogenic processes and therefore is a good organ to decipher the disease pathophysiology, which remains unclear. However, culturing primary skin cells is SSc can be a major issue due to small sample size combined to skin fibrosis. Here, we present a protocol allowing to isolate and culture the four main types of skin cells: dermal cells (microvascular dermal endothelial cells - HDMECs - and fibroblasts) and epidermal cells (keratinocytes and melanocytes), from a single 4mm-punch biopsy, at a low cost. The present protocol has been optimized to fit SSc skin cells particularities. Such technique allows to culture primary cells, crucial to study the disease pathophysiology, as well as to isolate cells in order to perform immediate molecular biology experiments such as single-cell transcriptomic. Cells grown from biopsies are also suitable for various types of experiments such as immunocytochemistry, Western blot, RT-qPCR or functional in vitro assays (angiogenesis, migration, etc). Ultimately, they can be used for experimental 3D cell culture models such as reconstructed skin.